The future of pesticides technology in agriculture: maximum target kill with minimum collateral damage - Omar, Dzolkhifli (Universiti Putra Malaysia Press, 2008)
Pesticides are widely used in agricultural production and have on human existence. They have been credited with increasing crop yields, protecting land and property, and even saving human lives. At the same time, pesticides are associated with some of the problems in agricultural production particularly those pertaining to pollution of the environment. The new paradigm in socio-environmental consciousness imposes on agricultural production to not only generate income but to be socially-responsible, sustainable and have minimum impact on the environment. In principle, sustainable agriculture espouses minimum use of pesticides, and only a last resort. However in practice, this seldom happens and pesticide usage is deemed a necessary evil especially in areas of heavy pest infestation. There is therefore a cogent need to reconcile the necessity of pesticide application with the damage visited on the ecosystem. Towards this end, this lecture will present the options of effective pesticide application with respect to choice, formulation and delivery technology for maximum impact with minimum collateral damage. Optimal dosage delivery that maximizes the biological effect on the target through the concept of controlled-release is one of the options to minimize the environmental impact of pesticides. Controlled-release of pesticides utilizes a depot system that continuously releases the active ingredient into the environment over a specified period of time. This would reduce the frequency of pesticide applications. Another novel approach to pest control is the use of biological pesticides or biopesticides. These are biorational (biologically rational) or ecorational substances that, when used for specific pests, have very limited or no effect on non-target organisms or the environment. The US Environmental Protection Agency defines them as any substances of natural origin that have a detrimental effect on specific target pests, possess a unique mode of action, and are non-toxic to man and the environment. They can either be living microbes and invertebrates, biochemical derived from living organisms The Future of Pesticides Technology in Agriculture or plant-incorporated protectants (eg transgenic Bt corn). The botanical insecticide, rotenone, extracted from the root of the tuba plant, Derris ellipfica has been shown to perform similarly to the standard synthetic compound. Similarly, entomopathogenic fungi from the Hyphomycetes, which are naturally responsible for epizootics (disease epidemics) in insect pest populations, Have good myco-insecticidal properties. Formulating the natural compound of entomopathogenic fung efficacy and ease of application in the field, minimizing handling hazards and accommodating the operational practices of Malaysian represents monumental allenges. The microemulsion of rotenone and water sible mefarhizium spores have been successfully formulated. A major problem in the application of pesticides is that a large proportion of the pesticide does not reach the target, with spray efficiency, particularly with insecticides, estimated to be less than 1%. Research in finding a solution that would have far reaching commercial and environmental implications has been directed to the spray volume application rate, selection of an appropriate atomizer and equipment calibration. The final product would be a precision equipment, calibrated to deliver the recommended dosage Of pesticide with an optimum spray droplet size and exact number dropletsper given area. This technology would vastly improve the efficiency of utilization of the active ingredients of the pesticide. The above development and research findings pave the way for the future not only in ensuring the most effective application of pesticides for crop protection, but also in enhancing food safety and protecting the ecosystem.